Architectural shop drawing of scope of CC3 & CC5 from 6th to 12th storey (RFA-371_Rev A) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of PDF version of drawings.